Stem Cell Transplantations Between Siblings as Social Phenomena The Child's Body and Family Decision-making - Schües, Christina; Rehmann-Sutter, Christoph; Jürgensen, Martina; Herzog, Madeleine (Philosophy and Medicine, 2022)
This open access book offers insights in short- and long-term experiences from families with bone marrow transplantations between minor siblings. It is based on the first extended qualitative study with 17 families about experiences with recent transplants and experiences with transplants up to 20 years in the past. It covers reflections of donors, recipients and other family members, as well as family interactions. Transplantation of bone marrow from one sibling to another who is ill with a blood cancer (such as Leukemia) is a life-saving therapy. Young children however are not in a position to give consent themselves. How should they be adequately included, depending to their age? Which ethical questions are raised for the parents both at the time of treatment and afterwards, and for the medical professionals in clinical and regulatory contexts? For an in-depth discussion of the findings the books brings together a group of leading scholars from the fields of bioethics, family sociology and philosophy of medicine.